The choice of the terms and methods of nitrogen additional fertilizing for winter bread wheat in the southern part of the Rostov region - A. A. Sukharev; G. M. Zelenskaya (Зерновое хозяйство России)
The current paper has presented the results of three years’ study (2012–2014) of the application of various terms and methods of nitrogen additional fertilizing for the winter bread wheat variety “Stanichnaya”. There has been studied efficiency of various terms and methods of nitrogen additional fertilizing with various forecrops. There has been identified an effect of these additional fertilizing on winter bread wheat productivity according to the forecrops. In the control variant, the productivity of the variety according to the forecrop depended greatly on the forecrops: 5.52 t/ha (weedfree fallow), 5.26 t/ha (peas), 4.29 t/ha (maize for grains) and 3.57 t/ha (winter wheat). There has been identified large productivity in the autumn ammonium nitrate fertilizing by the scattering method (in all variants of the forecrops), the productivity raised on 0.38–0.73 t/ha. The study has shown that the economic effect of the ammonium nitrate fertilizing in the autumn was also at maximum profitability, 76–154%, and the conditional net income was 10 675–22 955 rubles/ha. The efficiency of ammonium nitrate fertilizing by the scattering method in the spring on thawed/frozen soil was lower, the productivity increase ranged from 0.21 t/ha sown after peas to 0.65 t/ha sown after maize. Root additional fertilizing with a seeder gave a positive effect only when the variety was sown after for winter wheat and maize, in that case the productivity increase was 0.52 t/ha and 0.46 t/ha, respectively. The conditional net income in these variants exceeded the control variant on 1574–2123 rubles/ha. Carbamide (urea) additional fertilizing was only effective for the variety sown after maize, where the productivity increase was 0.40 t/ha, but profitability (100%) and conditional net income (16 593 rubles/ha) were lower than with ammonium nitrate fertilizing by the scattering method in the spring (112% and 18 080 rubles/ha respectively).